Alleviating Poverty in Sub-Saharan Africa: The Role of Inclusive Business Models. (17th April 2023) - Kamgnia, Bernadette Dia; Ahouré, Alban A E
Abstract: The study aimed to analyze the ability of inclusive business (IB) models to sustainably contribute to efforts made in alleviating poverty in Sub-Saharan Africa, with an emphasis on the cases of Côte d'Ivoire and Kenya. Data collected on these two countries revealed a clear opposite stream in the integration pattern of the populations at the bottom of the pyramid (BoP) in IB models. In Côte d'Ivoire individuals at BoPs integrate IBs mainly through the agricultural sector, getting busy with the supply of raw material, and with the distribution and/or sale of products in the value chain; thus, supporting an upstream integration. In Kenya, individual at BoPs rather are concentrated in manufacturing, with a first choice on non-permanent employees as activity in the value chain, followed by permanent employees; hence, downstreaming the integration ladder. In both countries, IB contributes positively and significantly to welfare at BoPs, especially when the IB model is implemented as part of a specific program.